2016
DOI: 10.1038/srep36815
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional label-free imaging and quantification of lipid droplets in live hepatocytes

Abstract: Lipid droplets (LDs) are subcellular organelles with important roles in lipid storage and metabolism and involved in various diseases including cancer, obesity, and diabetes. Conventional methods, however, have limited ability to provide quantitative information on individual LDs and have limited capability for three-dimensional (3-D) imaging of LDs in live cells especially for fast acquisition of 3-D dynamics. Here, we present an optical method based on 3-D quantitative phase imaging to measure the 3-D struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 61 publications
5
122
0
Order By: Relevance
“…However, XNH does not identify molecules or chemicals in the tissue, one added advantage of the modality is the ability to record quantitatively local refractive indices proportional to the local electron density, delivering data as known from quantitative phase imaging, for example, differential interference contrast microscopy,33 hard X‐ray grating interferometry,[[qv: 13a]] or 3D refractive index tomography 34…”
Section: Discussionmentioning
confidence: 99%
“…However, XNH does not identify molecules or chemicals in the tissue, one added advantage of the modality is the ability to record quantitatively local refractive indices proportional to the local electron density, delivering data as known from quantitative phase imaging, for example, differential interference contrast microscopy,33 hard X‐ray grating interferometry,[[qv: 13a]] or 3D refractive index tomography 34…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanisms of growth, movement, and biosynthesis of LDs have not been well understood. The fact that the RI values of LDs are distinctly higher than that of the cytoplasm offers TPM an opportunity to segment out LDs and act as a 3D label-free tool for their imaging and quantification [31,55,112]. Using TPM, Kim et al [55] obtained the time lapse of the 3D RI distributions of LDs inside a hepatocyte cell.…”
Section: Applicationsmentioning
confidence: 99%
“…The fact that the RI values of LDs are distinctly higher than that of the cytoplasm offers TPM an opportunity to segment out LDs and act as a 3D label-free tool for their imaging and quantification [31,55,112]. Using TPM, Kim et al [55] obtained the time lapse of the 3D RI distributions of LDs inside a hepatocyte cell. By 3D tracking of individual LDs over 93 s, they revealed that the diffusive motions of LDs have a great variety, ranging from sub-diffusion to active transport.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these label-free methods represent an improvement over fluorescent microscopy, a sophisticated instrumental setup is required and these methods are further limited by the relatively low signal intensity and long acquisition time required for Raman-based imaging techniques. Recently, three dimensional quantitative phase imaging of lipid droplets in hepatocytes was reported [21], but this method also requires a sophisticated instrumental setup and so far has only been applied to individual cells. Despite existing imaging methods for measuring lipid droplet size in cells and tissues, a label free method based on individual lipid droplet size measurements would reduce the bias introduced by limited throughput, alleviate the necessity of complex instrumental setup, and the use of lipophilic dyes, and allow the lipid droplets to be recovered for downstream analysis.…”
Section: Introductionmentioning
confidence: 99%